The June 2015 legislative election in Turkey - Cop, Mehmet Burak (Elsevier Sci Ltd, The Boulevard, Langford Lane, Kidlington, Oxford Ox5 1Gb, Oxon, England, 2016)
The Republic of Turkey held its first presidential election, which employed a universal suffrage based on popular vote, on 10 August 2014. Unlike most of the countries organizing separate ballots for electing the president and the MPs, Turkey did not hold both elections on the same day. Instead, the subsequent parliamentary election would be held ten months later, i.e. on 7 June 2015. The reason behind this is not only due to the differences of the term lengths between parliament and the President (which are four and five years respectively), but also the peculiarity in the inclusion of a "presidential element" (a president elected by popular vote) into a political regime which must still be seen as a parliamentary system. This oddness arose from the political crisis in 2007. (C) 2015 Elsevier Ltd. All rights reserved.